The Effect of Acupressure on The KI 3 on Pain Scale in Gout Arthritis Patients at UPTD PUSKESMAS I Health Office of Denpasar Selatan Subdistrict - Ni Wayan Somawati Purnamasari; Ni Komang Matalia Gandhari; Ni Luh Putu Dian Yunita Sari; Nyoman Eta Risnawati (Jurnal Kesehatan, 2025)
Introduction: Gout arthritis is a condition where there is an increase in uric acid levels in the blood, leading to various effects, one of which is pain. Managing pain in gout arthritis patients can be addressed through complementary therapy, one of which is acupressure on the KI 3 point. This study aims to determine the effect of acupressure on the KI 3 point on pain scale in gout arthritis patients at UPTD Puskesmas I Health Office of Denpasar Selatan Subdistrict. Method: The study was conducted using a pre-test and post-test one-group design from February to March 2025, with a sample size of 20 respondents selected using purposive sampling. Pre-test and post-test data were collected using a numerical rating scale. Data were analyzed using the Wilcoxon signed-rank test with p<0.05. Results: The results showed that the pain scale before acupuncture at point KI 3 had a median pain score of 5, and there was a change in the pain scale after acupuncture at point KI 3, with a median of 3. The analysis results indicate an effect of acupressure at the KI 3 point on the pain scale of gout arthritis patients at the UPTD Puskesmas I Health Center in Denpasar Selatan District, with a p-value <0.001. The recommendations from this study are expected to serve as input for nurses to always provide acupressure as a supportive therapy for gout arthritis patients to alleviate acute pain. Conclusion: It can be said that there was an effect of acupressure at the KI 3 point on the pain scale of gout arthritis patients at the UPTD Puskesmas I of the South Denpasar District Health Office with a value of p=0.001.